Exploration and morphologic variation of Iris wild species with ornamental potential - Asgari, Elham; Taghizadeh, Mina; Abbasifar, Ahmadreza (Ornamental Horticulture, 2021)
Nowadays, the flower industry is growing so fast that its development requires introducing new varieties to the flower market. Iran is the habitat of numerous species of wild plants that are among the valuable genetics in the breeding process. The identification of native Iris species, investigation of morphological diversity, and distribution method have a significant effect on the introduction of this flower as new and superior cultivars cut flower and bedding plant. The documentation of the most important habitats of Iris in Arak province, identification of morphological characteristics and correlation determination of morphological traits are the most important aims of this research. The results showed that there is a correlation between some of the traits. The highest positive correlation was related to the height of flower and length of the leaf, length of the flowering stem and the length of the leaf and the height of the flower and the length of the flowering stem. The ecotypes of Iris sp. were divided into six groups. Based on the results of the cluster diagram, the bulbous species were separated from rhizome species. Generally, due to the color diversity of Iris sp. and unique beauty of the flowers and the resistance of the native species, they can be used as native foundations. Due to the prominent traits such as high durability of Iris meda, odor of I. hymernospatha Subsp. leptoneura and color diversity of I. persica, I. songarica and height of I. spuria, they can be used to introduce new ornamental species. Iris spuria is the most suitable genotype because of the high height, large flower, high durability, and beautiful flower.